Revisiting the Nonprofit Property-Tax Exemption: An Examination of the Need to Clarify Eligibility - Corcuera, Daniella (Journal of Law and Commerce, 2013)
"Revisiting the Nonprofit Property-Tax Exemption: An Examination of the Need to Clarify Eligibility"